The content and effect of "psyching up" strategies in weightlifters - Shelton, T. O. (Cognitive Therapy and research, 1978)
Under various experimental manipulations, the best lifting performances were obtained under a "psych yourselves" treatment as opposed to baseline and distraction (counting backwards by 7's from a four-digit number) conditions. A post-experimental interview revealed the psyching strategies to be combinations of all or some self-efficacy statements, performance imagery, self-generated arousal, and attentional focus techniques. Implication: The best preparations occurred when the athlete controlled content and implementation. No external interaction, such as a coach talk, was necessary to promote the best performances.